Clinical practice recommendations for prehabilitation and post‐operative rehabilitation for arthroplasty: A scoping review. (14th February 2022) - Krysa, Jacqueline A.; Ho, Chester; O'Connell, Petra; Pohar Manhas, Kiran
Abstract: Background: The rising need for arthroplasty (joint replacement) has resulted in a significant increase in wait‐times. Longer surgical wait‐times may further exacerbate functional decline in adults with osteoarthritis as well as delay postoperative functional recovery. This review aims to better inform rehabilitation care provision before (prehabilitation) and after (post‐rehabilitation) hip or knee arthroplasty based on recommendations from clinical practice guidelines (CPGs). Methods: This scoping review used a three‐stage process to screen and extract articles, which resulted in 123 articles reviewed for analysis. Included CPGs were in the English language and focussed on rehabilitation interventions or practices involving adult patients preparing for or recuperating from hip and knee arthroplasty (published 2009–2020). Results: Patient assessments, use of assistive devices, as well as self‐management and education programs were recommended before and after arthroplasty. Physiotherapy was recommended to support post‐operative rehabilitation. Conversely, there was limited evidence supporting recommendations for or against physiotherapy during the prehabilitation phase of the arthroplasty care journey. Conclusions: The findings from this review highlight the current gap in high‐quality evidence supporting hip and knee arthroplasty rehabilitation CPGs before and after surgery. Findings warrant additional research to ensure patients are best prepared for surgery and supported for optimal recovery.